Relationships between hybrid performance and genetic distance revealed by morphological and AFLP marker in cucumber - Olfati , J. A.; Samizadeh , H.; Peyvast , Gh.; Rabiei , B.; Khodaparast , S. A. (Plant Breeding and Seed Science, 2012)
This study investigated the relationship of morphological and molecular genetic distance with hybrid performance and heterosis in cucumber in an attempt to make use of genetic distance in predicting hybrid performance. The results of this study showed that GD, in general, correlated poorly with heterosis and SCA. Results showed that the mean values of the hybrids were significantly larger or smaller for many traits when compared with the mean of parental lines, indicating that heterosis was present for these traits. In next step we compare inter group hybrids versus intra group hybrids. This test showed that intra group hybridization although increased the yield and yield component but decrease some fruit quality such as fruit color and shape.